Erratum to: Development of antimicrobial coating by later-by-layer dip coating of chlorhexidine-loaded micelles (Journal of Materials Science: Materials in Medicine, (2017), 28, 6, (90), 10.1007/s10856-017-5899-2) - Supreeda Tambunlertchai (2018)
© 2017, Springer Science+Business Media, LLC. The original version of this article unfortunately contained a typo in the title. The word “later-by-layer” in the title should read as “layer-by-layer”. It is now corrected with this erratum.